2021
DOI: 10.1177/0271678x21989186
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic underpinnings of activated and deactivated cortical areas in human brain

Abstract: Neuroimaging with functional MRI (fMRI) identifies activated and deactivated brain regions in task-based paradigms. These patterns of (de)activation are altered in diseases, motivating research to understand their underlying biochemical/biophysical mechanisms. Essentially, it remains unknown how aerobic metabolism of glucose to lactate (aerobic glycolysis) and excitatory-inhibitory balance of glutamatergic and GABAergic neuronal activities vary in these areas. In healthy volunteers, we investigated metabolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 93 publications
4
52
0
Order By: Relevance
“…12 Only one recently published study demonstrates the power of concurrent fMRI-fMRS measurements interleaving unsuppressed water acqusitions with water-suppressed J-difference editing acqusitions. 6 In this study, we demonstrated the BOLD induced line narrowing behavior due to brain activation in the MC water signal acquired simultaneously with the metabolite signals from the same voxel. The BOLD effect on water is easier to compute than on metabolites since metabolite peaks are overlapped by macromolecules and other metabolite resonances, which makes linewidths and peak heights determination challenging.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…12 Only one recently published study demonstrates the power of concurrent fMRI-fMRS measurements interleaving unsuppressed water acqusitions with water-suppressed J-difference editing acqusitions. 6 In this study, we demonstrated the BOLD induced line narrowing behavior due to brain activation in the MC water signal acquired simultaneously with the metabolite signals from the same voxel. The BOLD effect on water is easier to compute than on metabolites since metabolite peaks are overlapped by macromolecules and other metabolite resonances, which makes linewidths and peak heights determination challenging.…”
Section: Discussionmentioning
confidence: 70%
“…water-unsuppressed measurements in the same TR provide the closest link between hemodynamics and neurochemistry. 6,13,19,66 Since a 3D EPI sequence is used in the BOLD fMRI-MRS combining studies, activation maps with a high spatial resolution could be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be measured using functional magnetic resonance spectroscopy (fMRS), a technique which quantifies chemical compounds within a three-dimensional volume. As recent studies show, combining BOLD-fMRI with fMRS that records glutamate and lactate concentrations can help to dissect the neural processes at play in active brain areas ( Mangia et al, 2007 ; Schaller et al, 2014 ; Ip et al, 2017 ; Boillat et al, 2020 ; Koush et al, 2021 ).…”
mentioning
confidence: 99%